2018
DOI: 10.1148/radiol.2017162787
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MR Strain: A Noninvasive Biomarker of Fibrofatty Remodeling of the Left Atrial Myocardium

Abstract: Purpose To determine whether left atrial (LA) strain quantification with cardiac magnetic resonance (MR) imaging feature tracking is associated with the severity of LA fibrofatty myocardial remodeling at histologic analysis. Materials and Methods This prospective case-control study was approved by the institutional review board. LA strain was evaluated with cardiac MR feature tracking between January 2014 and March 2015 in 13 consecutive patients (mean age, 61 years ± 19; nine male) with mitral regurgitation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
2
21
0
1
Order By: Relevance
“…Associations of LA function with LV remodeling and LV longitudinal strain revealed that: 1) LA reservoir function seems to be a mixture of LA compliance impairment due to fibro-fatty infiltration in the LA myocardium as well as of LV longitudinal dysfunction. Indeed in the present study LA reservoir function seems to be related to LV longitudinal strain while it has been significantly associated to histological LA tissue characteristics in a previous study [12], 2) LA conduit phase might be mainly LV driven, 3) LA contraction phase strain indices were not linearly associated to LV remodeling but rather in a bi-phasic behavior indicating its ability to reflect the compensatory role of the LA to LV early filling but also the loss in LA myocardium contractility. Accordingly, while LA reservoir and conduit strains can be regarded as partially LV-driven indices, LA contraction strain can be regarded as an intrinsic LA function index.…”
Section: Discussionsupporting
confidence: 56%
“…Associations of LA function with LV remodeling and LV longitudinal strain revealed that: 1) LA reservoir function seems to be a mixture of LA compliance impairment due to fibro-fatty infiltration in the LA myocardium as well as of LV longitudinal dysfunction. Indeed in the present study LA reservoir function seems to be related to LV longitudinal strain while it has been significantly associated to histological LA tissue characteristics in a previous study [12], 2) LA conduit phase might be mainly LV driven, 3) LA contraction phase strain indices were not linearly associated to LV remodeling but rather in a bi-phasic behavior indicating its ability to reflect the compensatory role of the LA to LV early filling but also the loss in LA myocardium contractility. Accordingly, while LA reservoir and conduit strains can be regarded as partially LV-driven indices, LA contraction strain can be regarded as an intrinsic LA function index.…”
Section: Discussionsupporting
confidence: 56%
“…17 Additionally, LA strain, evaluated by cardiac magnetic resonance image, was shown a strong degree correlation with fibrofatty replacement at a histological level. 18 In our present study, larger EATi volume was closely associated with more impaired LA global longitudinal strain, regardless of confounding factors. EATi volume negatively correlated with 3D-LAEF and 3D-active LAEF.…”
Section: The Association Between Eat Volume and Impaired La Functionsupporting
confidence: 59%
“…Although dynamic magnetic resonance imaging (CINE MRI) has also been used to estimate global atrial function, these analyses have traditionally been based on one or two 8 to 10-mm thick 2D slices [9], [10]. This poor spatial coverage and resolution precludes an analysis of regional atrial strains, which are likely to be of important clinical value.…”
Section: Introductionmentioning
confidence: 99%